Strengthening HR Competence in the Indonesian National Police through Hybrid Assessment Centers (Enhancing Police Professionalism in the Era of Disruption) - Riantanti, Diah Ika; Zainal, Veithzal Rivai; Hakim, Azis (Manajerial, 2025)
This study aims to analyze the implementation of the Hybrid Assessment Center as a strategy to enhance the professionalism of human resources within the Indonesian National Police (Polri) through an innovative approach that combines traditional assessment methods with digital technology. This hybrid approach not only strengthens technical skills but also soft skills such as leadership, communication, and adaptability to change—skills that are crucial for success in the dynamic nature of police duties. The research employs a descriptive qualitative methodology, with data collection based on literature review and analysis of digital documents related to the implementation of the Hybrid Assessment Center within Polri. The findings indicate that the hybrid approach provides a more accurate and comprehensive assessment of individual competencies, fostering sustainable development. Additionally, the use of digital technologies, such as virtual reality and remote assessment, allows for more efficient and flexible evaluations, especially in crisis situations such as a pandemic. The study recommends emphasizing the integration of technology in human resource management within Polri and suggests continuous improvements to the competency assessment system via the Hybrid Assessment Center. The implementation of this model is expected to support the enhancement of Polri's human resource quality, making personnel more prepared to face the challenges of the disruptive era and ensuring professional service to the community.